2019
DOI: 10.3389/fpls.2019.01207
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the YABBY Gene Family in Grapevine and Functional Characterization of VvYABBY4

Abstract: Genes of the plant-specific YABBY transcription factor family have various roles, including lateral organ development, establishment of dorsoventral polarity, and response to abiotic stress. In this study, we carried out a genomic census of YABBY genes in grapevine (Vitis vinifera) and characterized their expression pattern during ovule development. We identified seven YABBY genes and classified them into five subfamilies, based on peptide sequence, similarity of exon–intron structure and composition of peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 70 publications
6
45
2
Order By: Relevance
“…In A. thaliana, YABBY genes are involved in floral and lateral organ development 40 , specifically the development of carpels and the ovule outer integument 41 . Though VviYABBY3 is not yet characterized, expression of V. pseudoreticulata VpYABBY1 and VpYABBY2 in A. thaliana (and of VvYABBY4 in tomato) implicates these genes in leaf and carpel development 27,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana, YABBY genes are involved in floral and lateral organ development 40 , specifically the development of carpels and the ovule outer integument 41 . Though VviYABBY3 is not yet characterized, expression of V. pseudoreticulata VpYABBY1 and VpYABBY2 in A. thaliana (and of VvYABBY4 in tomato) implicates these genes in leaf and carpel development 27,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the demand for seedless grapes is also increasing [23,24]. In recent years, scientists have reported genes such as VvYABBY4 and VvHB58 as having a role in grapevine fruit and seed development [25,26]. However, the key genes mediating this process still needs to be explored, such as, for example, GASA genes.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Batillana et al [57] indicated that a VVIB23 SSR marker, contained in the 3 UTR of the YABBY gene, has specific variations associated with specific phenotypes of the flower sex locus. More recently, Zhang et al [58] showed that VvYABBY3 (from the same VVI23 locus in chromosome 2) has an increased expression at the beginning of ovule abortion and Massonnet et al [51] found that YABBY was more highly expressed in male flowers compared to female and hermaphrodite flowers at pre-blooming and anthesis stages, suggesting that YABBY is associated with female sterility in grape, inhibiting ovule development. Transgenic expression of VvYABBY4 (that has a similar expression pattern as VvYABBY3) in tomatoes conferred reduced seed sizes associated with smaller endosperm cells, but without affecting the number of seeds per fruit [58]).…”
Section: Candidate Genesmentioning
confidence: 99%
“…More recently, Zhang et al [58] showed that VvYABBY3 (from the same VVI23 locus in chromosome 2) has an increased expression at the beginning of ovule abortion and Massonnet et al [51] found that YABBY was more highly expressed in male flowers compared to female and hermaphrodite flowers at pre-blooming and anthesis stages, suggesting that YABBY is associated with female sterility in grape, inhibiting ovule development. Transgenic expression of VvYABBY4 (that has a similar expression pattern as VvYABBY3) in tomatoes conferred reduced seed sizes associated with smaller endosperm cells, but without affecting the number of seeds per fruit [58]). In Vitis, VvβVPE, a vacuolar processing enzyme not located in chromosome 2, was described as having a caspase-1-like activity with the ability to regulate programmed cell death (PCD) and putatively playing an essential role in the development of stenospermocarpic seedless grapes ovules [59].…”
Section: Candidate Genesmentioning
confidence: 99%